Pengaruh Modifikasi Permainan Basdor terhadap Motivasi dan Minat Belajar Dribbling Bola Basket Siswa MAN 8 Jombang - Synthiawati, Novita Nur; Hendrawan, Kahan Tony (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Basdor is a modification of the basketball game combined with gobak sodor, which modifies the field, number of players, gameplay, playing time, and uses a ball. The research problem in this study is whether there is an influence of the modified basdor game on the motivation and interest in learning basketball dribbling among 10th-grade students of MAN 8 Jombang. The objective of this research is to determine the influence of the basdor game on the motivation and interest in learning basketball dribbling among 10th-grade students of MAN 8 Jombang. The method used in this study is pre-experimental design. The research design employed is a one-group pretest-posttest design, which means that the research activity involves an initial test (pretest) before treatment, and after the treatment is administered, a final test (posttest) is conducted. The one-group pretest-posttest design consists of one predetermined group with no control group. Based on the results of calculations using prerequisite tests, namely descriptive tests, normality tests, homogeneity tests, and hypothesis testing, the hypothesis test results show a t-value of 5.850 and a t-table value of 1.711. Thus, the t-value of 5.850 is greater than the t-table value of 1.711. Therefore, there is an influence of the modified basdor game on the motivation and interest in learning among 10th-grade students of MAN 8 Jombang.